The Values of Islamic Education Philosophy "Adat Besandi Syarak, Syarak Besandi Kitabullah" in Kampung Sakti Rantau Batuah - Saputra, M.Fachdir; Sirait, Sangkot; Karwadi, Karwadi; Nurchamidah, Nurchamidah; Hamsah, Muhammad (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2023)
This study discusses the understanding of the traditional philosophy of "adat besandi syarak, syarak besandi kitabullah" in the community of Kampung Sakti Rantau Batuah, Mukomuko City District, Mukomuko Regency, Bengkulu Province. Aims to know and understand the Philosophical Values of Islamic Education "Adat Bersendi Syarak, Syarak Bersendi Kitabullah" in Kampung Sakti Rantau Batuah. The research method used in this study is qualitative descriptive. Data were obtained using semi-structured interview methods related to indigenous philosophies and implications of Islamic Education philosophy. The informants of this study consisted of traditional leaders, religious leaders, community leaders, and tribal leaders. The informant technique was carried out using a purposive sampling technique conducted by the head of the BMA (Customary Consultative Board) of Mukomuko district. The results of the study found that the philosophy of adat besandi syarak, syarak besandi kitabuallah, has two meanings, namely: first, adat bersandi syarak means customs that are by Islamic sharia and do not contradict the teachings of Islam, Sharak besandi Kitabullah means sharia sourced from kitabullah (Quran and hadith). Among the existing educational philosophy, values including Honesty and a clean heart are the characteristics of the leadership of Rasulullah SAW. This is the same hope desired by the Mukomuko Community in the leadership in the Mukomuko area. The higher a person's degree, the more burdens and responsibilities he will face. He needs patience and should not be arrogant. Every Mukomuko community is a brother who is attached, and a strong brotherhood symbolizes kinship, and strong kinship is evidenced by the brotherhood between indigenous people who are bound together.